2015
DOI: 10.1002/pssc.201510040
|View full text |Cite
|
Sign up to set email alerts
|

Titania‐based photocatalytic coatings on stainless steel hospital fixtures

Abstract: A scaled-up pulsed-pressure MOCVD system was used to deposit TiO 2 coatings from tetra-isopropoxide precursor solution on stainless steel substrates and on 3-D objects. The objective of the work is the production of antimicrobial coatings for handles in health care facilities. Antimicrobial coatings are sought to manage the transmission of hospital acquired infections (HAI's), which are reported to cost around one million pounds per annum in the UK alone. Titania is a promising material for this application du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Brevet et al [ 23 ] observed a pyramidal shape morphology for 500 nm thick TiO 2 film on Si by MOCVD. Krumdieck et al [ 9 , 29 ] deposited very thick TiO 2 film (2 µm) on fused silica by PP-MOCVD and obtained (T = 400 °C) prismatic top structures about 200–250 nm wide. Although with different reaction conditions in terms of pressure and precursor supply (T = 350 °C and 20 min deposition time), Zhang et al [ 30 ] deposited TiO 2 film on 310S stainless steel by AP-MOCVD, observing a similar morphology with faceted prismatic grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brevet et al [ 23 ] observed a pyramidal shape morphology for 500 nm thick TiO 2 film on Si by MOCVD. Krumdieck et al [ 9 , 29 ] deposited very thick TiO 2 film (2 µm) on fused silica by PP-MOCVD and obtained (T = 400 °C) prismatic top structures about 200–250 nm wide. Although with different reaction conditions in terms of pressure and precursor supply (T = 350 °C and 20 min deposition time), Zhang et al [ 30 ] deposited TiO 2 film on 310S stainless steel by AP-MOCVD, observing a similar morphology with faceted prismatic grains.…”
Section: Resultsmentioning
confidence: 99%
“…Only one record is found using “industrial scale up and TiO 2 and MOCVD” as key words [ 7 ]. Moreover, the papers are mainly focused on atmospheric pressure or pulsed pressure reactors [ 7 , 8 , 9 ] rather than LP-MOCVD. Atmospheric pressure reactors are more attractive from an industrial perspective because of their simplified management.…”
Section: Introductionmentioning
confidence: 99%
“…The pp-MOCVD method is scalable, produces conformal films on a variety of substrates and allows control of the microstructure of films by changing deposition conditions [12]. Previous work on microstructural development of pp-MOCVD titania films has focused on the effect of processing parameters including substrate temperature and dose per pulse on mature films [13,14]. Functional performance of pp-MOCVD films has been evaluated in two studies: water splitting efficiency was studied for a series of titania films grown at a single temperature on FTO (fluorine doped tin oxide) -coated glass [2], and antimicrobial activity was evaluated for a titania film on stainless steel [15].…”
Section: Introductionmentioning
confidence: 99%